Ethical Politics and the Revival of Islamic Teaching in Indonesia - Tamwifi, Irfan; Akbar, Eliyyil; Rahman, Mohd Nazri Abdul (Didaktika Religia, 2024)
This article aims to elucidate the interconnection between ethical politics and the resurgence of Islamic doctrine in Indonesia, which serves as the foundation for the enduring tradition of Islamic doctrine. The development of Islam in Indonesia is seldom connected to the history of colonialism. Nevertheless, numerous transformations in Islamic thought and teaching occurred in close proximity to the implementation of ethical policies in the late colonial era. This study employs a qualitative methodology with a historical anthropological perspective. The research data is derived exclusively from historical literature and is analysed in accordance with Foucault's theory of power relations. The study concludes that ethical politics exerts an indirect influence on the resurgence of Islamic teachings. The aversion to all things European among Islamic circles has resulted in the importation of comprehensive Islamic teachings from the Middle East as a foundation for the evolution of Islamic teachings in Indonesia. This article posits that colonial ethics played a role in the resurgence of Muslim intellectuals and reinforced the standing of Islamic education in Indonesia.